2000
DOI: 10.1097/00005392-200006000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Progression of Stage T1, Grade 3 Transitional Cell Carcinoma of the Bladder Following Intravesical Immunotherapy With Bacillus Calmette-Guerin

Abstract: Adjuvant immunotherapy with BCG after complete transurethral resection of bladder tumor represents a highly effective primary treatment of stage pT1, grade 3 carcinoma of the bladder. Immediate radical cystectomy does not appear necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…The recurrence and progression rates observed in our series were comparable with those observed by others [29] ( table 5 ). A significant proportion of our patients, including the pT1 G3 patients, were tumor-free following the full course of BCG.…”
Section: Tumors Before Treatmentsupporting
confidence: 92%
See 2 more Smart Citations
“…The recurrence and progression rates observed in our series were comparable with those observed by others [29] ( table 5 ). A significant proportion of our patients, including the pT1 G3 patients, were tumor-free following the full course of BCG.…”
Section: Tumors Before Treatmentsupporting
confidence: 92%
“…Lifelong meticulous surveillance is mandatory for these patients. Reported series of BCG intravesical immunotherapy for pT1 bladder cancer [29] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High grade pT1 bladder neoplasm (pT1HG) really represents a therapeutic challenge due to the high risk of progression (about 15-30%) to muscle-invasive disease, usually within 5 years (6). However, no consensus exists regarding the treatment of patients with recurrent bladder tumours that invade the lamina propria (pT1) (7)(8)(9). Recent studies suggested that the first cTURBT may be incomplete in a significant number of cases (10).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of BCG therapy is to eradicate the disease and to inhibit tumor recurrence and prevent the progression of cancer (4)(5)(6). Although used in large number of patients, the immunotherapy mechanism of action of BCG has remained a black box for three decades.…”
Section: Introductionmentioning
confidence: 99%